The relation between extreme doubly stochastic operators and extreme doubly stochastic matrices. - Shahidi, Farruh (s.n, 2012)
Doubly stochastic quadratic operators are put into correspondence with doubly stochastic matrices. It is shown that the operator is extreme only if the corresponding matrix is extreme. Besides, it is studied the limiting behavior of doubly stochastic operators.